Pemberdayaan UMKM melalui Pendampingan Pendaftaran Produk Platform Marketplace Shopeefood di Kecamatan Benowo. - Ahmad Yusuf Bin Yasir Ba amir; Nurkholish Majid (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main factors in the regional economy, especially in urban areas. However, there are still various obstacles faced by MSME players, particularly in the use of digital technology for marketing activities, including the use of marketplace platforms. This community service activity was organized with the aim of improving the quality of MSMEs in Benowo District, Surabaya, through assistance with the registration process and product management on the ShopeeFood application. The activity was carried out in several stages, namely providing material on digital marketing marketplaces, training on creating ShopeeFood accounts, assistance in uploading products, and evaluation of the success of the registration process. The results of this activity showed an increase in the knowledge and ability of MSME players in utilizing the marketplace platform as a digital-based marketing medium. MSME players successfully registered their businesses on ShopeeFood and began marketing their products online. This assistance has had a positive impact on increasing the visibility of MSME products and opening up opportunities to expand their market reach. Therefore, assistance with product registration on the ShopeeFood marketplace can be an effective effort in encouraging digital transformation and strengthening MSMEs in Benowo District, Surabaya.